She’s Got Nice Smile: Enacting Personal Photograph in Teaching Descriptive Writing - Moch. Imam Machfudi (Journal of Languages and Language Teaching, 2023)
English teachers agreed that developing their students’ writing ability was the most chalenging than the other abilities This study explores the components of effective teaching descriptive writings. Specifically, this research examines a classroom practice of an English teacher at the State Islamic Junior High School (Madrasah Tsanawiyah) in Jember, East Java. This study focuses on how the English teacher enacted personal photograph in teaching writing and to investigate the students’ perceptions toward the use of personal photograph in writing descriptive text. This study, which employs qualitative research, portrays the reality that occurs in the field related to the enactment of personal photographs in teaching writing descriptive text. There was a successful modelling of personal photograph based on students’ views toward the learning that almost all beneficial. Aside from the successful practice, this research found minor drawbacks although did not impede the classroom practice.